2016
DOI: 10.1016/j.njas.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of home garden model for year round production and consumption for improving resource-poor household food security in Bangladesh

Abstract: The government of Bangladesh has long been striving to increase food security and to reduce poverty and malnutrition. In this regard, home gardens can play an important role in providing enhanced food supply and increased diversity of food to some extent. Studies on niche/ecosystem based homestead gardening were carried out at Lahirirhat Farming Systems Research and Development site, Rangpur under the On-Farm Research Division of Bangladesh Agricultural Research Institute during 2008-2009, resulting in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 20 publications
5
59
0
2
Order By: Relevance
“…large crop gross margin) could help to cover the larger food costs linked to desirable nutritional outcomes. This is in line with Greiner (2017) who found that a food-based approach 1 is a cost-efficient strategy to improve nutritional status, particularly in areas where multiple nutrients are deficient. Nonetheless, our results also suggest that home-garden diversification could also lead to maximize income generation rather than nutritional outcomes, as is already the case in the area.…”
Section: Nsa Interventions and Potential Development Pathwayssupporting
confidence: 86%
See 1 more Smart Citation
“…large crop gross margin) could help to cover the larger food costs linked to desirable nutritional outcomes. This is in line with Greiner (2017) who found that a food-based approach 1 is a cost-efficient strategy to improve nutritional status, particularly in areas where multiple nutrients are deficient. Nonetheless, our results also suggest that home-garden diversification could also lead to maximize income generation rather than nutritional outcomes, as is already the case in the area.…”
Section: Nsa Interventions and Potential Development Pathwayssupporting
confidence: 86%
“…low iron or calcium contributions). Empirical evidence in Bangladesh indicates the feasibility of tripling home garden production and vegetable consumption (Ferdous et al 2016). In this modelling study we estimated that improving household nutrient adequacy could be reached by almost doubling on-farm contributions to household consumption, although the large consumption of the Selected Crops for nutritional outcomes (i.e.…”
Section: Nsa Interventions and Potential Development Pathwaysmentioning
confidence: 94%
“…The data were analyzed using t-test and statistical analytical techniques such as descriptive, frequency, percentage and graphs in line with Ferdous et al (2016). Economic analysis was made using partial budget analysis which was done to determine the economic feasibility of the weed control methods.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (Ferdous and Islam, 2008;Kabir et al, 2017a;Ferdous et al, 2016) have also reported that homestead gardens and diversified farming systems are most profitable for marginal and small farmers in Bangladesh.…”
Section: On Farm Demonstration Results Of Optimum Farm Planmentioning
confidence: 93%